2021
DOI: 10.3892/mi.2021.27
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of nucleo‑cytoplasmic transport factor exportin 1 in malignancy

Abstract: Nuclear pore complexes (NPCs) regulate the entry and exit of molecules from the cell nucleus. Small molecules pass through NPCs by diffusion while large molecules enter and exit the nucleus by karyopherins, which serve as transport factors. Exportin-1 (XPo1) is a protein that is an important member of the karyopherin family and carries macromolecules from the nucleus to the cytoplasm. XPo1 is responsible for nuclear-cytoplasmic transport of protein, ribosomal rNa and certain required mrNas for ribosomal biogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…It can be used in the development of new treatment strategies for laryngeal cancer patients with increased CRM1 expression level. Dysregulation of CRM1 has been shown to be associated with increased expression in many types of cancer, particularly solid tumors [ 19 ]. As far as we know, this is the first study to report elevated CRM1 expression as an independent prognostic marker for poor clinical course and overall survival in laryngeal cancer patients diagnosed with squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It can be used in the development of new treatment strategies for laryngeal cancer patients with increased CRM1 expression level. Dysregulation of CRM1 has been shown to be associated with increased expression in many types of cancer, particularly solid tumors [ 19 ]. As far as we know, this is the first study to report elevated CRM1 expression as an independent prognostic marker for poor clinical course and overall survival in laryngeal cancer patients diagnosed with squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Nuclear transcription factor Y (NFY)/CREB-binding protein (CBP), Sp1 transcription factor (SP1), and tumor protein p53 (P53) transcription factors interact with the promoter of the CRM1 gene and together play an important role in the transformation of cancer cells [ 46 ]. In previous studies, it has been reported that the specific inhibition of CRM1 increases the nuclear uptake and expression of major tumor suppressor proteins such as RB, P53, P21, P33, FOXO, P27, and decreases the expression of oncogenic proteins such as MYC, MET, and EGFR [ 9 , 10 , 19 ]. CRM1 is the solo nuclear transporter of many proteins with prognostic value in laryngeal cancer, such as P53, P16, P63, Rb, PTEN, Nuclear factor kappa B (NFκB), EGFR, Cyclin D1, Survivin, and BCL-2 [ 9 , 19 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations